Detection of follistatin‐based inhibitors of the TGF‐β signaling pathways in serum/plasma by means of LC‐HRMS/MS and Western blotting. Issue 11 (12th October 2020) - Walpurgis, Katja; Weigand, Tim; Knoop, Andre; Thomas, Andreas; Reichel, Christian; Dellanna, Frank; Thevis, Mario
Abstract: Cytokines of the transforming growth factor beta (TGF‐β) superfamily such as myostatin and activin A are considered as key regulators of skeletal muscle mass. In vivo, their activity is controlled by different binding proteins such as follistatin (FST), whose interaction with the circulating growth factors prevents activation of the activin type II receptors. FST‐based protein therapeutics are therefore not only promising drug candidates for the treatment of muscular diseases but also potential performance‐enhancing agents in sports. Within this study, two complementary detection assays for FST‐based inhibitors of the TGF‐β signaling pathways in doping control serum and plasma samples were developed by using both monomeric FST and dimeric FST‐Fc fusion proteins as model compounds. The initial testing procedure is based on immunoaffinity purification, tryptic digestion, and LC‐HRMS/MS, offering high specificity by targeting tryptic signature peptides of FST. As the glycoprotein is also produced endogenously, the confirmation method employs immunoaffinity purification, sodium dodecyl sulfate polyacrylamide gel electrophoresis, and Western blotting in order to detect the intact proteins and differentiate synthetic FST‐Fc constructs from naturally occurring FST isoforms. Both assays were found to be highly specific with an estimated detection limit of 10 ng/ml. Moreover, a commercial sandwich enzyme‐linked immunosorbent assay was used to determine endogenous FST values. The detected FST serum levels of healthy volunteers were found below 5 ng/ml, which is in accordance with reference values from the literature and below the doping control detection methods' limit of detection (LOD). The presented assays expand the range of available tests for emerging doping agents, and the initial testing procedure can readily be modified to include further protein drugs. Abstract : Follistatin‐based TGF‐β inhibitors are not only promising drug candidates for the treatment of muscle wasting disorders, but also potential performance‐enhancing agents in sports. Within this research project, two complementary detection assays for follistatin‐based protein therapeutics in doping control serum and plasma samples were developed by using immunoaffinity purification in combination with tryptic digestion and LC‐HRMS/MS or SDS‐PAGE and Western blotting. Both approaches were found to be highly specific with an estimated detection limit of 10 ng/ml.